The influence of management innovation, school ethos and community engagement on school quality - Cahyani, Arini Dwi; Riyanto, Yatim; Karwanto, Karwanto (Edelweiss Applied Science and Technology, 2025)
This research aims to prove the direct and indirect influence of management innovation, school ethos, and community engagement on school quality. The Equation Modeling (SEM) model test analysis technique was used. Research results: 1) Strengthens Scheerens’ organizational theory that school organizations can show four indicators, declared as a school with a good level of school quality model. 2) The level of achievement of one of the focuses or paths of school quality is at the level of learning in schools and classes that are oriented towards student achievement. 3) Based on the findings and the novelty of the research results, the achievement of school quality on the path of achievement and success of students is influenced and determined by management innovation, school ethos, and community involvement directly, with management innovation being the key factor directly in the non-formal education path, specifically in the type of CLC education in East Java. These factors contribute directly to student achievement and success through strengthening achievement orientation, consistency, and change management in the context of non-formal education. CLC managers need to strengthen management innovation, school ethos, and community involvement to improve the quality of educational services and student achievement.